Ijtihād - Amīnī, Muḥammad Taqī (Qadīmī Kutabḵẖānah, 2002)
Critical interpretation of Islamic jurisprudence according to changing time and circumstance.
Ijtihād kā tārīḵẖī pas manẓar -- Masʼlah-yi ijtihād par taḥqīqī naẓar.
Critical interpretation of Islamic jurisprudence according to changing time and circumstance.
In Urdu.
Keywords: Islamic law / Interpretation and construction. / http://id.loc.gov/authorities/subjects/sh85068455